A Retrospective Study Comparing the Outcome of Horses Undergoing Small Intestinal Resection and Anastomosis With A Single Layer (Lembert) or Double Layer (Simple Continuous and Cushing) Technique. Issue 4 (1st April 2014) - Close, Kristyn; Epstein, Kira L.; Sherlock, Ceri E.
<x xml:space="preserve">Abstract</x> Objectives To (1) compare postoperative complications and survival in horses after small intestinal resection and anastomosis using 2 anastomosis techniques (single layer Lembert; double layer simple continuous oversewn with Cushing), and (2) to compare outcome by anastomosis type (jejunoileostomy; jejunojejunostomy). Study Design Retrospective case series. Animals Horses (n = 53). Methods Medical records (July 2006–July 2010) of all horses that had small intestinal resection and anastomosis. Horses were divided into groups based on technique and type of anastomosis. Comparisons of pre‐ and intraoperative findings (disease severity), postoperative complications, and survival rates were made between groups. Results There were no differences in disease severity, postoperative complications, or survival between single layer (n = 23) or double layer (n = 31) anastomoses. There were no differences in disease severity or survival between jejunoileostomy (n = 16) or jejunojejunostomy (n = 38). There was a higher incidence of postoperative colic in hospital after jejunoileostomy (13/16) compared with jejunojejunostomy (18/38) (P = .0127). Conclusions Postoperative complications and survival are comparable between horses undergoing single layer and double layer small intestinal end‐to‐end anastomoses. With the exception of increased postoperative colic in the hospital, postoperative complications and survival after jejunoileostomy and jejunojejunostomy are also comparable.